Media Literacy on Prevention of Pornography Effects through Personal Social Responsibility at Gerendong Village Pandeglang-Banten - Kholisoh, Nur; Ganiem, Leila Mona; Mijan, Rohana (Jurnal Abdi Masyarakat (JAM), 2023)
The social problem that is rife today is related to the impact of pornography on social media among children and adolescents. Pornography has a very big danger, especially teenagers. Adolescent psychology is still unstable and the growth of sexual hormones in adolescents, making pornography has a danger (negative impact) is very large on adolescents. Not only drugs that contain addictions, pornography also makes viewers addicted / addicted. For teens, addicted to porn sites (cybersex) will make learning rhythm become chaotic. In general, addiction to porn sites will have a negative impact on one's character. Based on research by Bingham and Piotrowski in the Psychological Report entitled On-line Sexual Addiction, the character of people who are addicted to cybersex are: Inadequate social skills, preferring to wrestle with sexual fantasy, engrossed in communication with the characters created by him. own imagination, and unable to control themselves not to access porn sites and forget time. The results of a Child Protection Commission (KPA) survey of 4,500 teenagers revealed, 97 percent of teens had watched or accessed pornography and 93 percent kissed their lips. Like chemical addiction, pornography addicts tend to replace something important with sex or other forms of pornography. People who are addicted to pornography usually use media such as magazines, porn videos or most often is the internet. Adolescents who generally still live with parents, therefore the role of supervision from parents is needed to provide an understanding of the use of social media wisely and directed to use social media positively. Parents can only provide gadgets as an easy access for their children to explore YouTube social media, but basically they also lack understanding about the media so there is still a lack of awareness for parents to control the content that their children see and consume on social media YouTube. Therefore, the need for media literacy training among adolescents is a form of prevention of the impact of pornography on YouTube social media in Gerendong Village, Pandeglang - Banten